PENGARUH LATIHAN INTERVAL TRAINING TERHADAP PENINGKATAN DAYA TAHAN PADA PEMAIN SEPAK BOLA SSB GARUDA TALENT FOOTBALL UJUNG TANJUNG ROKAN HILIR - Zainudin, Zainudin; Ramadi, Ramadi; Aspa, Agus Prima (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The aim of this research is to determine the effect of introductoryInterval Training exercises on the endurance of SSB Garuda Talent Football UjungTanjung Rokan Hilir football players. Based on the t test analysis, it produces tcount of20.29 and Ttable of 1.796. This means tcount>ttable, and based on statistical dataanalysis there is a pre-test average of 44.38 and a post-test average of 49.25. It can beconcluded that the athlete's ability is influenced by the training interval trainingrequired to support the frequency of training in improving endurance performance.Based on the results of the findings and data processing above, it can be concluded asfollows: There is an influence of Interval training (X) on the endurance ability (Y) ofSSB Garuda Talent Football Ujung Tanjung Rokan Hilir football players. Based on theresearcher's view of endurance abilities, Interval training training skills can reapmaximum results because of the habits carried out by each individual athlete.Key Words: Interval training, increasing endurance, football.